Rice and global climate change - Wassmann, Reiner; Nelson, Gerald C.; Peng SB; Sumfleth K; Jagadish, Krishna S.V.; Hosen Y; Rosegrant, Mark W. (International Rice Research Institute, 2010)
Climate change has many facets, including changes in long-term trends in temperature and rainfall regimes with increasing year-to-year variability and a greater prevalence of extreme events. The effects of these changing conditions on agriculture are already being seen, yet there are still considerable gaps in our knowledge of how agricultural systems will be affected directly or indirectly by the changing climate, and what implications these changes will have for rural livelihoods (IPCC 2007). Climate change gives an additional burden to the world’s agricultural and natural resource systems that must already cope with the growing food demand driven by population growth and higher incomes in developing countries. The challenge is compounded by the uncertainty and pace of climate change and its effects regionally. It is increasingly clear that climate change will affect agricultural productivity. The temperature and precipitation changes that accompany climate change will require farmers to adapt, but precisely where and how much is uncertain. At the same time, as a signiﬁcant contributor of greenhouse gases and a potential sink for atmospheric carbon, agriculture can help mitigate climate change. In this chapter, we discuss the issues for rice agriculture in a world where climate change is increasingly a reality. The purpose of this review is to provide a comprehensive overview on (1) the expected impacts on rice production at different scales, (2) possible mitigation and adaptation options available to rice farmers, and (3) the economic implications of climate change and climate change policy. Many of the impacts of climate change on rice production discussed in this review are applicable to other food crops as well, but, in spite of these commonalities, we highlight several “rice-speciﬁc” aspects that warrant an in-depth discussion of the impacts of climate change as well as possible adaptation and mitigation options.